(untitled) (Scientia Agricola, 2002)
Seed production usually requires fast decisions to improve the efficacy of seed handling during harvesting, processing and storage. Seed technologists have focused on the development or improvement of procedures which allow rapid and consistent identification of higher quality seed lots. This research verified the effectiveness of the potassium leachate test on the evaluation of the physiological potential of maize seeds in comparison to recommended seed vigor tests. Five seed lots of the hybrid Avant were submitted to the potassium leachate, standard germination, first count, accelerated aging, electrical conductivity, field emergence and cold tests. The amount of potassium leachate was determined after seed imbibition for 30, 60, 90, 120, 150 and 180 minutes, at 25°C; a flame photometer adjusted to 50 mug K+ mL-1 pattern and reading 50 was used to determine the amount of leached potassium. The potassium leachate test consistently ranked the seed lots according to their physiological quality in comparison to other tests, and is a new alternative test for maize seed quality control programs.